New electrodes for old: from carbon nanotubes to edge plane pyrolytic graphite. - Banks, C; Compton, R (2006)
Different types of carbon based electrodes have emerged over the last few years, significantly changing the scope and sensitivity of electro-analytical methods for the measurement of diverse targets from metal ions through gases to biological markers. This Highlight article shows how the use of carbon nanotube modified electrodes has led to a fundamental understanding of the location and nature of electron transfer processes on graphitic electrodes and to the realisation that edge plane pyrolytic graphite may represent, at present, an optimal electrode material of this type for electroanalysis.